1968
DOI: 10.1103/physrev.167.1062
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Moment ofRb85: Resolving a Discrepancy

Abstract: The ratio of the nuclear gi factor to the atomic gj factor in 86 Rb has been measured by the atomic-beam magnetic-resonance technique to be g/(uncorr)/gj-= -1. 466478 (22) X10~4. This result is in excellent agreement with recent optical-pumping measurements but is lower than a previously reported atomic-beam result. R ECENT optical-pumping determinations of gi/gj for free 85 Rb atoms 1 are in considerable disagreement with an earlier atomic-beam measurement of the same ratio. 2 Because the discrepancy between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1968
1968
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…The gj/gj (Rb 85 ) value is in agreement with the recent atomicbeam value. 5 The low value of magnetic field available in this work coupled with the observation of only AF = 0 Zeeman transitions precluded a severe test of the Breit-Rabi formula. Nevertheless, the agreement between calculated and observed frequencies (for transitions other than those used in gj/gj determinations) was in general ~ 5 parts in 10 9 .…”
Section: Discussionmentioning
confidence: 83%
“…The gj/gj (Rb 85 ) value is in agreement with the recent atomicbeam value. 5 The low value of magnetic field available in this work coupled with the observation of only AF = 0 Zeeman transitions precluded a severe test of the Breit-Rabi formula. Nevertheless, the agreement between calculated and observed frequencies (for transitions other than those used in gj/gj determinations) was in general ~ 5 parts in 10 9 .…”
Section: Discussionmentioning
confidence: 83%
“…The agreement is satisfactory, and this is especially true between the two most accurate measurements. Penselin et al (1962) have also carried out a measurement of gz/gz, that has been found to be in considerable disagreement with later measurements by White et al (1968) and by Ehlers et al (1968). Nevertheless, the hfs measurement by Penselin et al (1962) seems to be reliable.…”
Section: ] »Rbmentioning
confidence: 80%
“…Table 4 shows a comparison of the data on determining the rubidium nuclear magnetic moment from the papers [1][2][3][4][5] and the data of the present paper. The results of the papers [1][2][3][4][5] were later included in reference publications [6,7] after being corrected for the nuclear electron screening.…”
Section: Comparison Of Data On Rubidium Nuclear Magnetic Momentsmentioning
confidence: 99%
“…Data on the rubidium nuclear magnetic moments were previously obtained: by optical excitation method with radio frequency detection [1] (OP/RD method); by the nuclear magnetic resonance method [2] (NMR−H 2 O method); recording of frequency resonance on rubidium nuclei in an atomic beam [3] (method AB/D); methods of laser spectroscopy in atomic beams [4] (method ABLS) and NMR method at dissolution of rubidium in heavy water [5] (method NMR−D 2 O). However, after the required corrections for the electron screening of the nuclei [6,7], it turned out that the data [1][2][3][4][5] diverge in units of the fifth or quadruple sign, and when calculating the nuclear magnetic moment of rubidium isotopes µ( 85 Rb) and µ( 87 Rb) not all components of the uncertainty were correctly taken into account.…”
Section: Introductionmentioning
confidence: 99%